Bio-based chitosan/PVdF-HFP polymer-blend for quasi-solid state electrolyte dye-sensitized solar cells - Yahya, W.Z.N. (European Polymer Federation, 2017)
Dye-sensitized solar cells (DSSCs) have emerged to become one of the most promising alternatives to conventional solar cells. However, long-term stability and light-to-energy conversion efficiency of the electrolyte in DSSCs are the main challenges in the commercial use of DSSCs. Current liquid electrolytes in DSSCs allow achieving high power conversion efficiency, but they still suffer from many disadvantages such as solvent leakage, corrosion and high volatility. Quasi-solid state electrolytes have therefore been developed in order to curb these problems. A novel polymer electrolyte composed of biobased polymer chitosan, poly(vinylidene fluoride-hexafluoropropylene) (PVdF-HFP), 1-methyl-3-propylimidazolium iodide ionic liquid and iodide/tri-iodide redox salts in various compositions is proposed in this study as a quasi-solid state electrolyte. Fourier transform infrared microscopy (FTIR) studies on the polymer electrolyte have shown interactions between the redox salt and the polymer blend. The quasi-solid state electrolyte tested in DSSCs with an optimised weight ratio of PVdF-HFP:chitosan (6:1) with ionic liquid electrolyte PMII/KI/I2 has shown the highest power conversion efficiencies of 1.23 with ionic conductivity of 5.367×10-4 S·cm-1 demonstrating the potential of using sustainable bio-based chitosan polymers in DSSCs applications. © 2017 Walter de Gruyter GmbH, Berlin/Boston.